2019
DOI: 10.3892/mmr.2019.10898
|View full text |Cite
|
Sign up to set email alerts
|

Anti‑proliferative effect of cardamonin on mTOR inhibitor‑resistant cancer cells

Abstract: a number of mammalian target of rapamycin (mTor) inhibitors have been approved for the treatment of certain types of cancer or are currently undergoing clinical trials. However, mTor targeted therapy exerts selective pressure on tumour cells, which leads to the preferential growth of resistant subpopulations. There are two classes of mTor inhibitors: i) The rapalogs, such as rapamycin, which bind to the 12-kda FK506-binding protein/rapamycin-binding domain of mTor; and ii) the aTP-competitive inhibitors, such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…Several studies have reported that cardamonin exerts its cytotoxic activity via inhibition of mTOR signalling [22][23][24]. A further study showed that cardamonin reduced the expression level of phosphorylated Akt, which is an upstream regulator of mTOR [25].…”
Section: Compound 19 Exerted Its Cytotoxic Activity In Mda-mb-468 and Panc-1 Cells Via Inhibition Of Akt/4ebp1 Signalling And Downregulatmentioning
confidence: 97%
“…Several studies have reported that cardamonin exerts its cytotoxic activity via inhibition of mTOR signalling [22][23][24]. A further study showed that cardamonin reduced the expression level of phosphorylated Akt, which is an upstream regulator of mTOR [25].…”
Section: Compound 19 Exerted Its Cytotoxic Activity In Mda-mb-468 and Panc-1 Cells Via Inhibition Of Akt/4ebp1 Signalling And Downregulatmentioning
confidence: 97%
“…However, further experiments are required to con rm the relationship between ROS production and apoptosis induction by 19 in the cancer cells. Several studies have reported that cardamonin exerted its cytotoxic activity via inhibition of mTOR signaling [23][24][25]. A further study has shown that cardamonin reduced the expression level of phosphorylated Akt, which is an upstream regulator of mTOR [26].…”
Section: Compound 19 Induced Caspase-dependent Apoptosis and Ros Genementioning
confidence: 98%
“…Furthermore, CD downregulated cyclin D1 and activated caspase-3, and suppressed xenograft breast tumors in mice (Kong et al., 2019). Recent studies have shown that CD inhibited breast cancer cell growth and proliferation via targeting HIF-1α and mTOR/p70S6K pathway ( Jin et al., 2019 ; Niu et al., 2020 ).…”
Section: Biological Activities Of CDmentioning
confidence: 99%